Features and outcome of familial idiopathic pulmonary fibrosis - Ravaglia, Claudia; Tomassetti, Sara; Gurioli, Christian; Piciucchi, Sara; Dubini, Alessandra; Gurioli, Carlo; Casoni, Gian Luca; Romagnoli, Micaela; Carloni, Angelo; Tantalocco, Paola; Buccioli, Matteo; Chilosi, Marco; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Idiopathicpulmonary fibrosis (IPF) has a sporadic occurrence in most instances,but can also occasionally occur in familial form. While clinicalfeatures of sporadic IPF are well defined, clinical presentation,complications, and outcome of familial IPF are still undefined. Thisretrospective study was undertaken to establish clinical parametersand survival time in a consecutive series of patients with familialIPF and to establish whether the phenomenon of anticipation could beobserved.  Methods:30 patients had received a diagnosis of familial IPF at ourinstitution over the period from January 2005 and December 2011; in7 of them there was a parent–child relation.Clinical features and patient outcome were analyzed and contrasted toa well characterized cohort of 127 patients with non familial IPF.Results:there was no significant difference in presenting symptoms and theoverall outcomes were quite similar in the two groups, but thefamilial group was much more enriched for females and we found astatistically significant lower age at onset in the youngergenerations (mean age 57,8 years versus 74,2 years, p 0,001). Acuteexacerbations, IPF progression and lung cancer were more frequent inthe familial IPF group as a cause of death (p < 0,005).Conclusion:familial IPF seems indistinguishable from sporadic IPF with respectto most clinical and physiologic findings; however the age of onsetwas slightly lower among the familial cases than in the sporadiccases of IPF and the phenomenon of anticipation could be observed.